On the Question of Functioning and Existence of Portrait Drawings by Hans Holbein the Younger - Istomina, Nadezhda A. (Actual Problems of Theory and History of Art, 2017)
The main function of Holbein’s drawing is supporting, purely practical one. However, there are several facts proving that it is not their only function. The 16th century is a period of the heyday of humanism taking an active interest in history as well as interpreting the biography of personalities and the memory of humanactivities. Holbein’s use of tinted paper giving the effect of warm carnation, the correction of used drawings and the fact that Holbein didn’t make preparatory study for the portraits of the representatives of the merchant class allow us to conclude that he considered a drawing as a complete work included into the “gallery” of the humanists that he depicted. This gallery represents the master’s relationships, the breadth of his creativity, and the artist’s excellence. A well-known story claimimg that the painting of Thomas More’s family bearing its members’ names and ages was brought by Holbein to Erasmus Roterodamus shows that the drawing assumes not only a historical but also a documentary function. The fact that Hans Holbein the Younger’s works were collected by his friend — a Basel humanist Bonifacius Amerbaсh, and later by his son Basilius who founded “Amerbach-Kabinett“ in Basel in 1578, confirms the aesthetic function of portrait drawings which were transformed from preparatory materials into the objects having an artistic value.
Keywords: German art; Renaissance; Holbein; portrait; drawing; creative method; preparatory study; Erasmus Roterodamus; Amerbach; Thomas More; humanism